The Mint Of Callatis In The Hellenistic Period. Stages And Possible Models Of Presence, Penetration And Possible Monetary Circulation In The Greco-Native Environment - Talmațchi, Gabriel Mircea (Acta Archaeologica Lodziensia, 2019)
The city of Callatis, founded by colonists of Heraclea Pontica, probably in the second half of the 6th century BC, experienced a special period of economic and urban development during the 4th century BC. With its resource-rich agricultural hinterland, the colony sustained a dynamic trade with important commercial centres (Heraclea, Sinope, Thasos, Rhodes etc.). During the second half of the 4th century BC, the local and regional context favoured the opening of a mint that initially struck silver (drachmas, half drachmas and quarter drachmas), then gold (staters) and silver (tetradrachms), as well as bronze coins of various iconographic types. Chronologically, Callatis is the second coin-issuing centre on the west coast of the Dobrudja after Istros. The presence, penetration and possible circulation of monetary issues from Callatis, during the 4th-1st centuries BC, can be traced step by step in different geographic areas, which closely correlate to the directions of trade developed by the colony in different chronological phases. What is noteworthy for the isolated discoveries is, during the fourth century, the widespread distribution of the bronze coins of the city, which are found in overwhelming proportions if we compare them with finds of Greek, Greek-native and native issues (particularly as regards the territory south of the Danube).